Use of technologies for monitoring and preventing cervical neoplasms: Integrative literature review (Research, Society and Development, 2022)
Objective: To identify the use and impacts of technologies for monitoring and preventing cervical cancer in primary health care. Method: Integrative literature review, using the databases: Scielo, Lilacs and BDFEN, considering the years 2011 to 2021, 373 articles were initially found in the databases, after applying inclusion and exclusion criteria to the sample of this study had 11 articles. Results: During the study, there was a greater use of light and light-hard technologies in the screening of cervical cancer. The most used technologies are "Manual control books", "CCU Tracking Program Indicators", "Educational Technology", "Educational Phone Call and Reminder", "Active Search", "Invitation Card", "Musical Development", “Educational approach” and “Reception”, we had some significant results with the use of these technologies in a short period of time. However, for long-term management and control, hard technology proved to be more efficient. With technological advances, it is possible to develop control tools through the use of mobile applications, software and other technologies. Final considerations: The use of technologies in health care services is still an obstacle to be overcome in Brazil. Science and technology are fundamental for the prevention and treatment of diseases and also for health organization and management. In this way, we believe that to ensure that all women have access to screening tests, in addition to light and light-hard technological interventions, greater investment in hard technology is necessary.